Integrating Legacy Laboratory Information Systems into a Client-Server World: The University of Minnesota Clinical Workstation (CWS) Project - Willard, K. E.; Sielaff, B. H.; Connelly, D. P. (Methods of Information in Medicine, 1995)
The development of an innovative clinical decision-support project such as the University of Minnesota’s Clinical Workstation initiative mandates the use of modern client-server network architectures. Preexisting conventional laboratory information systems (LIS) cannot be quickly replaced with client-server equivalents because of the cost and relative unavailability of such systems. Thus, embedding strategies that effectively integrate legacy information systems are needed. Our strategy led to the adoption of a multi-layered connection architecture that provides a data feed from our existing LIS to a new network-based relational database management system. By careful design, we maximize the use of open standards in our layered connection structure to provide data, requisition, or event messaging in several formats. Each layer is optimized to provide needed services to existing hospital clients and is well positioned to support future hospital network clients.
Keywords: Legacy Systems; Integration; Client-server; Open Systems; HL7; TCP; Object-Oriented Programming; Laboratory Information Systems